Comparative transcriptomics provide insight into the morphogenesis and evolution of fistular leaves in Allium - Zhu, Siyuan (BMC Genomics, 2017)
BACKGROUND: Fistular leaves frequently appear in Allium species, and previous developmental studies have proposed that the process of fistular leaf formation involves programmed cell death. However, molecular evidence for the role of programmed cell death in the formation of fistular leaf cavities has yet to be reported. RESULTS: In this study, we characterized the leaf transcriptomes of nine Allium species, including six fistular- and three solid-leaved species. In addition, we identified orthologous genes and estimated their Ka and Ks values, in order to ascertain their selective pattern. Phylogenetic analysis based on the transcriptomes revealed that A. tuberosum was the most ancestral among the nine species, and analysis of orthologous genes between A. tuberosum and the other eight species indicated that 149 genes were subject to positive selection; whereas >3000 had undergone purifying selection in each species. CONCLUSIONS: We found that many genes that are potentially related to programmed cell death either exhibited rapid diversification in fistular-leaved species, or were conserved in solid-leaved species in evolutionary history. These genes potentially involved in programmed cell death might play important roles in the formation of fistular leaf cavities in Allium, and the differing selection patterns in fistular- and solid-leaved species may be responsible for the evolution of fistular leaves. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-3474-8) contains supplementary material, which is available to authorized users.